Tensile strained direct bandgap GeSn microbridges enabled in GeSn-on-insulator substrates with residual tensile strain - Burt, Daniel (2023)
Despite having achieved drastically improved lasing characteristics by harnessing tensile strain, the current methods of introducing a sizable tensile strain into GeSn lasers require complex fabrication processes, thus reducing the viability of the lasers for practical applications. The geometric strain amplification is a simple technique that can concentrate residual and small tensile strain into localized and large tensile strain. However, the technique is not suitable for GeSn due to the intrinsic compressive strain introduced during the conventional epitaxial growth. In this Letter, we demonstrate the geometrical strain amplification in GeSn by employing a tensile strained GeSn-on-insulator (GeSnOI) substrate. This work offers exciting opportunities in developing practical wavelength-tunable lasers for realizing fully integrated photonic circuits.